2013
DOI: 10.1021/ie402999k
|View full text |Cite
|
Sign up to set email alerts
|

In Situ CO2 Capture Using CaO/γ-Al2O3 Washcoated Monoliths for Sorption Enhanced Water Gas Shift Reaction

Abstract: In situ capture of CO 2 allows the thermodynamically constrained water gas shift (WGS) process to operate at higher temperatures (i.e., 350°C) where reaction kinetics are more favorable. Dispersed CaO/γ-Al 2 O 3 was investigated as a sorbent for in situ CO 2 capture for an enhanced water gas shift application. The CO 2 adsorbent (CaO/γ-Al 2 O 3 ) and WGS catalyst (Pt/γ-Al 2 O 3 ) were integrated as multiple layers of washcoats on a monolith structure. CO 2 capture experiments were performed using thermal gravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…To overcome the limitation of conventional packed beds, structured catalysts such as monoliths, 14,15 structured fibrous networks, 16‐18 and structured foams 13,19‐23 have been studied to mitigate the effect by heat/mass transfer on chemical transformation and separation processes, including catalysis such as catalytic CO 2 methanation. For example, Ni catalysts supported on ceria‐zirconia coated foams (including open‐cell silicon carbide (SiC), alumina and aluminium foams) and carbon felt were developed and assessed for promoting catalytic CO 2 methanation, and heat regulation 20,24 .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the limitation of conventional packed beds, structured catalysts such as monoliths, 14,15 structured fibrous networks, 16‐18 and structured foams 13,19‐23 have been studied to mitigate the effect by heat/mass transfer on chemical transformation and separation processes, including catalysis such as catalytic CO 2 methanation. For example, Ni catalysts supported on ceria‐zirconia coated foams (including open‐cell silicon carbide (SiC), alumina and aluminium foams) and carbon felt were developed and assessed for promoting catalytic CO 2 methanation, and heat regulation 20,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the in-situ separation of H 2 , CO 2 removal has been confirmed as another promising route to promote the WGS reaction for H 2 production. Typically, CO 2 sorbents were used for in situ CO 2 removal to enhance the reaction performance [20][21][22]. It is also highly desirable to use a CO 2 -selective membrane for the WGS reaction because CO 2 -selective membrane reactors have the potential to achieve higher H 2 recovery [5].…”
Section: Introductionmentioning
confidence: 99%
“…[1,[12][13][14][15][16][17][18] These CaO-based chemisorbents appear to have similar working capacities, tolerance to steam, and cyclic working capacities, but poorer regeneration capabilities compared to their Na 2 O (periodic group I)-based counterparts. At the time of writing, only one study by Duyar et al has demonstrated that support CaO sorbents can be regenerated at temperatures as low as 350 8C.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of writing, only one study by Duyar et al has demonstrated that support CaO sorbents can be regenerated at temperatures as low as 350 8C. [18] The separation, capture, and storage of CO 2 , the major greenhouse gas, from industrial gas streams has received considerable attention in recent years because of concerns about environmental effects of increasing CO 2 concentration in the atmosphere. An emerging area of research utilizes reversible CO 2 sorbents to increase conversion and rate of forward reactions for equilibrium-controlled reactions (sorption-enhanced reactions).…”
Section: Introductionmentioning
confidence: 99%